STRATEGI PENGUATAN MANAJEMEN PENDIDIKAN AGAMA ISLAM BERBASIS MADRASAH UNTUK MEWUJUDKAN GENERASI QUR’ANI DAN BERKARAKTER DI MA PLUS MIFTAHUL ULUM LUMAJANG - Siti Aisyah; Nurul Iflaha; Imaniar Mahmuda; Hairul Ulum ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2026)
The development of digital technology has brought various moral challenges for Generation Z. This condition requires madrasahs as Islamic educational institutions to strengthen the role of Islamic Religious Education (PAI) through systematic management based on Qur’anic values. This Community Service Program (PKM) aimed to strengthen madrasah-based Islamic Religious Education management in fostering a Qur’anic and character-oriented generation at MA Plus Miftahul Ulum Lumajang. The implementation employed a participatory and practical approach consisting of lectures, question-and-answer sessions, interactive discussions, Qur’an reading practices, and implementation-oriented mentoring. The results of the program indicated an increased understanding among participants regarding the importance of integrating Islamic Religious Education management with the madrasah’s vision, religious culture, and student character development. Furthermore, teachers were able to develop learning instruments that integrated tilawah (Qur’an recitation), tahfidz (Qur’an memorization), tadabbur (Qur’anic reflection), and the internalization of moral values. At the institutional level, the madrasah demonstrated a commitment to integrating Qur’anic programs into the academic calendar and implementing a sustainable character evaluation system.